Reality and fiction: creative dysfunctions - García Lozano, Francisco José (Razón y fe, 2018)
Reality and fiction constitute the creative act. Their borders are not always clear and they are usually very subtle. Three recent films that really evidence it are: Ruby Sparks, The Words and In the House.
Keywords: reality; fiction; creative act; Ruby Sparks; The Words and In the House